2019
DOI: 10.1002/app.47590
|View full text |Cite
|
Sign up to set email alerts
|

In situsynthesized chitosan–gelatin/ZnO nanocomposite scaffold with drug delivery properties: Higher antibacterial and lower cytotoxicity effects

Abstract: In this work, chitosan–gelatin/zinc oxide nanocomposite hydrogel scaffolds (CS–GEL/nZnO) were prepared via in situ synthesis of ZnO nanoparticles (nZnO) to reach a scaffold with both inherent antibacterial and drug delivery properties. The prepared nanocomposite hydrogel scaffolds were characterized using scanning electron microscopy, transmission electron microscopy, atomic absorption spectrometer, Fourier transform infrared spectroscopy, and X‐ray diffraction. In addition, swelling, biodegradation, antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Accordingly, the presence of ZnO NPs at low concentrations in a textile coating did not compromise the cell viability, suggesting their high biocompatibility [75], and the capping of ZnO NPs with plant extracts further reduced their cytotoxicity [86]. A comparison of the effects of different coating procedures on ZnO cytotoxicity showed that the in situ synthesis of ZnO could importantly decrease its cytotoxicity compared to the deposition of previously synthesized ZnO to a polymer matrix [133]. The reason for this was attributed to the good distribution and superior performance of the in situ synthesized ZnO within the polymer matrix in comparison with the previously synthesized and agglomerated ZnO, causing its decreased cytotoxicity.…”
Section: Antimicrobial Propertiesmentioning
confidence: 97%
“…Accordingly, the presence of ZnO NPs at low concentrations in a textile coating did not compromise the cell viability, suggesting their high biocompatibility [75], and the capping of ZnO NPs with plant extracts further reduced their cytotoxicity [86]. A comparison of the effects of different coating procedures on ZnO cytotoxicity showed that the in situ synthesis of ZnO could importantly decrease its cytotoxicity compared to the deposition of previously synthesized ZnO to a polymer matrix [133]. The reason for this was attributed to the good distribution and superior performance of the in situ synthesized ZnO within the polymer matrix in comparison with the previously synthesized and agglomerated ZnO, causing its decreased cytotoxicity.…”
Section: Antimicrobial Propertiesmentioning
confidence: 97%
“…The hexagonal wurtzite crystal form of pure ZnO is significantly used in many industrial and practical applications. Rakhshaei et al reported that ZnO NPs with hexagonal phase show significant photocatalytic properties [63]. When a photon having energy greater than the band gap energy of ZnO strikes on its surface, electrons are released.…”
Section: Photocatalytic Activity Of Zno Npsmentioning
confidence: 99%
“…In some of preceding studies about antibacterial agents, efficiency of chitosan, silver based antimicrobial finishing processes and metallic salts for different end uses were tested by different methods. Additionally, nanocomposites including chitosan were synthesized using some components (chitosan–gelatin/zinc oxide, chitosan–TiO 2 –polyaniline) and their antibacterial activities were tested . There are also some patent studies for antibacterial treatment of reusable or disposable medical products (wound dressing, pads, diapers, wet wipes, tampons, bed clothes, underwear, etc.)…”
Section: Introductionmentioning
confidence: 99%